Robots and Worker Voice: An Empirical Exploration - Filippo Belloc; Gabriel Burdin; Fabio Landini (Institute of Labor Economics (IZA), 2020)
The interplay between labour institutions and the adoption of automation technologies remains poorly understood. Specifically, there is little evidence on how the nature of industrial relations shapes technological choices at the workplace level. Using a large sample of more than 20000 European establishments located in 28 countries, this paper documents conditional correlations between the presence of employee representation (ER) and the use of automation technologies. We find that ER is positively associated with robot usage. The presence of ER also correlates with the utilization of software-based artificial intelligence tools for data analytics. We extensively dig into the mechanisms through which ER may foster the use of robots by exploiting rich information on the de facto role played by ER bodies in relation to well-defined decision areas of management. Greater automation in establishments with ER does not seem to result from more adversarial employment relationships (as measured by past strike activity) or constraints on labour flexibility imposed by the interference of employee representatives with dismissal procedures. Interestingly, the positive effect of ER on robot usage is driven by workplaces operating in relatively centralized wage-setting environments, where one would expected a more limited influence of ER on wages. While our findings are exploratory and do not have a causal interpretation, they are suggestive that ER influences certain workplace practices, such as skill development, job redesign and working time management, that may be complementary to new automation technologies.
Keywords: J50; O32; O33; 330; automation; robots; artificial intelligence; unions; employee representation; labor market institutions; European Company Survey